2012
DOI: 10.1038/onc.2012.530
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pY654-β-catenin as a critical co-factor in hypoxia-inducible factor-1α signaling and tumor responses to hypoxia

Abstract: Hypoxia is linked to epithelial mesenchymal transition (EMT) and tumor progression in numerous carcinomas. Responses to hypoxia are thought to operate via hypoxia-inducible factors (HIFs), but the importance of co-factors that regulate HIF signaling within tumors is not well understood. Here we elucidate a signaling pathway that physically and functionally couples tyrosine phosphorylation of β-catenin to hypoxia-inducible factor-1α (HIF1α) signaling and HIF1α-mediated tumor EMT. Primary human lung adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…Consistent with hypoxia being a frequent feature of the microenvironment of infected tissues due to activation of the hypoxia-inducible factor and NF-κB pathways, 18,19 CR-infection-induced Hif-1α expression that coincided with relative increases in Hif-1α levels during hypoxia, in addition to induction of HDAC3, β-catenin, Slug and Snail (Supplementary Figure 2A). During wound-healing assay, N-acetylcysteine, an inhibitor of reactive oxygen species activity that is elevated during hypoxia, 44 inhibited CR-induced cell migration under normoxic conditions [Figure 3e(i), e(ii)]. During hypoxia, although CR-induced cell migration was recorded within 6 h, CR only partially rescued N-acetylcysteine-induced inhibition of cell migration [Figure 3f(i), f(ii)] due in part to decreases in β-catenin, Slug and Snail (Supplementary Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with hypoxia being a frequent feature of the microenvironment of infected tissues due to activation of the hypoxia-inducible factor and NF-κB pathways, 18,19 CR-infection-induced Hif-1α expression that coincided with relative increases in Hif-1α levels during hypoxia, in addition to induction of HDAC3, β-catenin, Slug and Snail (Supplementary Figure 2A). During wound-healing assay, N-acetylcysteine, an inhibitor of reactive oxygen species activity that is elevated during hypoxia, 44 inhibited CR-induced cell migration under normoxic conditions [Figure 3e(i), e(ii)]. During hypoxia, although CR-induced cell migration was recorded within 6 h, CR only partially rescued N-acetylcysteine-induced inhibition of cell migration [Figure 3f(i), f(ii)] due in part to decreases in β-catenin, Slug and Snail (Supplementary Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…5557 We now provide evidence of CR-induced EMT of immortalized, but primary, epithelial cells that promotes cell migration and intriguingly exhibits responses that mimic changes recorded during hypoxia. Given that hypoxia/Hif-1α regulates metastatic processes, especially EMT by directly interacting with β-catenin 44,58 or Notch intracellular domain, 59 it is not surprising that CR infection that mimics hypoxia and is associated with activation of the Wnt/β-catenin 30,34 and Notch 35,36 pathways, promotes neoplasia in response to a second hit. 36,45 Finally, several recent studies have shown that it is not unprecedented for EMT to generate cells with many of the properties of self-renewing stem cells (7–9).…”
Section: Discussionmentioning
confidence: 99%
“…The best evidence for the aforementioned model involves a tyrosine phosphorylation in β-catenin at residue 654, which leads to reduced E-cadherin binding both in vitro (Roura et al, 1999) and in vivo (van Veelen et al, 2011), and enhanced nuclear signaling activity (Jean et al, 2009; Kim et al, 2009; Piedra et al, 2001; van Veelen et al, 2011; Xi et al, 2013). Activation of a number of kinases is associated with phosphorylation of β-catenin at Y654, including EGFR (Jean et al, 2009), HGF (David et al, 2008), TGFβ (Kim et al, 2009), and Src downstream of a variety of signals (Condello, Cao, & Matei, 2013; Lee et al, 2013; Sumiyoshi, Takahashi, Obata, Sugimoto, & Kohara, 2011; Xi et al, 2013).…”
Section: Cadherin Nuclear Signaling Via Rtksmentioning
confidence: 99%
“…Activation of a number of kinases is associated with phosphorylation of β-catenin at Y654, including EGFR (Jean et al, 2009), HGF (David et al, 2008), TGFβ (Kim et al, 2009), and Src downstream of a variety of signals (Condello, Cao, & Matei, 2013; Lee et al, 2013; Sumiyoshi, Takahashi, Obata, Sugimoto, & Kohara, 2011; Xi et al, 2013). In most of these cases, pY654 β-catenin shows reduced association with cadherin contacts as well as enhanced nuclear accumulation and target-gene activation.…”
Section: Cadherin Nuclear Signaling Via Rtksmentioning
confidence: 99%
“…Thus, FOXO3a might suppress EMT of ccRCC cells and thereby inhibited metastasis. We searched for a panel of key regulators of EMT, including TWIST1, HIF1a, SNAIL1, and YBX1 (20)(21)(22)(23). These genes were all transcription factors that regulated EMT.…”
Section: Attenuation Of Foxo3a Activated Emt Through the Upregulationmentioning
confidence: 99%